Enteritis necrótica aviar y su comprobación en Colombia - Morales, Gustavo A.; Bustos M., Francisco; Díaz, Miguel A. (1971)
Necrotic enteritis in poultry was diagnosed histopathologically for the first time, in two chicken farms located in the Sabana de Bogotá, Cundinamarca, Colombia. Descriptions and comments are made of two outbreaks taking into account the clinical history, macroscopic and microscopic lesions and treatment established each of them